Development of scratch-based mathematics learning media on algebra - Surtiah Surtiah; Turmudi; Eyus Sudihartinih (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study aimed to develop Scratch-based mathematics learning media entitledSpongeBob Squad in Algebra Wonderland and describe initial users’ responses to the media. The product was developed using the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The initial trial involved 18 third semester pre-service mathematics teachers selected through convenience sampling at a university in Bandung. Data were collected using an open-ended questionnaire and semi-structured interviews and were analyzed through thematic coding and percentages of positive responses. The results showed that the algebra learning game was successfully developed through all MDLC stages. The participants gave an average positive response of 99%, categorized as very good. The appearance indicator received 94% positive responses, while programming, material, language, interest, and usefulness each received 100%. These findings indicate that the prototype received very favorable initial evaluations and was considered engaging, easy to operate, conceptually relevant, and useful for mathematics learning. However, trials involving junior high school students and classroom-based effectiveness studies are still required before broader implementation.